An insight into the temporal dynamics in the gut microbiome, metabolite signaling, immune response, and barrier function in suckling and weaned piglets under production conditions - Lerch, Frederike; Yosi, Fitra; Vötterl, Julia C.; Koger, Simone; Ehmig, Juliane; Sharma, Suchitra; Verhovsek, Doris; Metzler-Zebeli, Barbara U. (Frontiers in Veterinary Science, 2023)
Little information is available on age- and creep feeding-related microbial and immune development in neonatal piglets. Therefore, we explored age- and gut-site specific alterations in microbiome, metabolites, histo-morphology, and expression of genes for microbial signaling, immune and barrier function in suckling and newly weaned piglets receiving sow milk only or were additionally offered creep feed from day of life (DoL) 10. The experiment was conducted in two replicate batches. Creep feed intake was estimated at litter level. Piglets were weaned on day 28 of life. Gastric and cecal digesta and jejunal and cecal tissue were collected on DoL7, 14, 21, 28, 31 and 35 for microbial and metabolite composition, histomorphology and gene expression. In total, results for 10 piglets (n=5/sex) per dietary group (sow milk only versus additional creep feed) were obtained for each DoL. The creep feed intake was low at the beginning and only increased in the fourth week of life. Piglets that were fed creep feed has less lactate and acetate in gastric digesta on DoL 28 compared to piglets fed sow milk only (P < 0.05). Age mainly influenced the gastric and cecal bacteriome and cecal mycobiome composition during the suckling phase, whereas the effect of creep feeding was small. Weaning largely altered the microbial communities. For instance, it reduced gastric Lactobacillaceae and cecal Bacteroidaceae abundances, and lowered lactate and short-chain fatty acid concentrations on DoL31 (P < 0.05). Jejunal and cecal expression of genes related to microbial and metabolite signaling, and innate immunity showed age-related patterns that were highest on DoL7 and declined until DoL35 (P < 0.05). Weaning impaired barrier function and enhanced antimicrobial secretion by lowering the expression of tight junction proteins and stimulating goblet cell recruitment in jejunum and cecum (P < 0.05). Results indicated that age-dependent alterations, programmed genetically and by the continuously changing gut microbiome, had a strong impact on expression of genes for gut barrier function, integrity, innate immunity and SCFA signaling, whereas creep feeding little influenced the microbial and host response dynamics at the investigated gut sites.